Two-step synthesis of ca-based MgO hybrid adsorbent for pontential CO2 capturing application - Mohd Daud, Farah Diana; Ahmad, Nurul Amirah Izzati; Mahmud, Mudrikah Asif; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim (Trans Tech Publications Ltd, 2020)
Carbon capture and storage (CCS) is one of the method in reducing carbon dioxide (CO2) emissions into the atmosphere. CO2 capturing using calcium oxide (CaO) solid sorbents has been considered as an advanced concept for CO2 capture and recovery. However, the adsorption capacity of CaO decreases during repeated adsorption/desorption cycles. The stability of Ca-based sorbents during cyclic runs can be achieved via the incorporation of inert support materials. Among the available inert materials, MgO is most promising for CO2 due to high stability and a high Tammann temperature. Most of Ca- based MgO hybrid adsorbent synthesis methods sorbent come with its own limitations which are longer synthesis duration and complex or multistep methods. In this research, Ca-based MgO hybrid adsorbent was prepared via two-step method. Calcium acetate and magnesium nitrate as precursor had dissolved in water, follow by addition of ethanol. The mixture then became gelated and proceeded for calcination at 550oC and 650°C. The prepared sorbent was characterized by Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD) and fourier transfer infrared spectroscopy (FTIR). The XRD analysis of the Ca-based MgO hybrid adsorbent showed the existence of MgO,CaO and CaCO3. FTIR analysis showed existant of CaO bond and MgO bond. The morphology of the hybrid adsorbent was found to be spherical to granular shape and agglomerated. The Ca- based MgO hybrid adsorbent structural and morphological shows great potential for CO2 capturing capacity over multiple carbonation cycles for CO2 capturing application.